Organizational commitment: Does religiosity matter? - Muhammad Farrukh; Chong Wei Ying; Nazar Omer Abdallah Ahmed (Cogent Business & Management, 2016)
Purpose: The purpose of this study is to investigate the relationship between three dimensions of organizational commitment, namely; affective commitment, normative commitment, and continuance commitment. Method: Data were collected by the use of a structured questionnaire. Five hundred questionnaires were distributed and 306 usable questionnaires were collected back. Structural equation modeling was used to statistically test the model. We used SmartPLS V 2 software to assess measurement and structural model. Findings and contribution: The findings showed a positive relationship between religiosity, affective and normative commitment while no association was found between religiosity and continuance commitment. The study contributed to the domain of religion and organizational management by empirically testing the impact between the variables. To the best of the researchers' knowledge, there is no empirical study has been conducted on the said variables to date. Implication: Religion is a system of beliefs which effects attitude and behavior of the individual not only in society but also in work place. Keeping the religion and employees separate in work place is similar to keeping the mind away from the body. We believe that man is triune creature, thus organizations must encourage the people to bring their whole self in to give their maximum. Limitation: This study only focused on the higher educational institutes for gathering the data and ignored the other sectors, which limits the application of the findings on other sectors. Moreover, as the study was conducted in Pakistan where majority of the population belong to Islam, thus we can say the majority of respondents answered the survey by keeping the Islamic teaching in mind which made the limited generalizability of findings.
Keywords: 650